FAKTOR YANG MEMPENGARUHI HASIL BELAJAR SISWA MENGGUNAKAN ANALISIS DISKRIMINAN MI NURUL IMAN KOTA TANGERANG SELATAN - Sulaeman Sulaeman (LPPM Universitas Bina Bangsa, 2021)
This study aims to determine what factors influence learning achievement. This study aimed to create a discriminant model of learning achievement from the influencing factors. The object of this research is the students of MI Nurul Iman, South Tangerang City. The variables used are six variables. The dependent variable in this study is the average report card, while the independent variables are motivation (X1), Learning Methods (X2), Teacher Competence (X3), Parental Environment (X3), School Infrastructure (X5), Community Environment (X6), which used as many as 56 samples. Based on the results of the output of the discriminant model using the SPSS version 21 program, it shows that the factors that affect student learning outcomes are School Facilities (X5). The discriminant model formed to determine the discriminant function is from the factors that affect learning achievement. Apart from 1, these variables are not used. Then the following function is obtained: D = -3,980 + 0,369X5